ANALISIS KEBUTUHAN KOMPETENSI MAHASISWA TEKNIK INFORMATIKA BERDASARKAN STANDAR COMPUTING CURRICULA 2020 STUDI KASUS PADA MAHASISWA TEKNIK INFORMATIKA, UNIVERSITAS PALANGKA RAYA - Zahra Majidiah, Kumala; Imanuel, Rangga; Parhusip, Jadiaman (TEKTONIK : Jurnal Ilmu Teknik, 2024)
This study analyzes the competency needs of Informatics Engineering students at the University of Palangka Raya based on the Computing Curricula 2020 (CC2020) standards. The research aims to evaluate the alignment of the existing curriculum with global standards and identify areas for improvement. The study employs a descriptive analysis method with both quantitative and qualitative approaches, involving students, lecturers, and industry experts as respondents. The findings reveal that most technical competencies, such as programming, data structures, and networking systems, are adequately covered. However, there are gaps in mastering emerging technologies like big data, artificial intelligence, and cloud computing, as well as non-technical skills such as communication and teamwork. In conclusion, the Informatics Engineering curriculum at the University of Palangka Raya needs to be updated by adding relevant courses, involving industry in curriculum development, and enhancing lecturer training to meet global industry demands.